Nations and nationalism : a reader - Spencer, Philip; Wollman, Howard (Edinburgh University Press, 2005)
Nationalism is a key area of political theory, with a huge amount of literature available. This text includes both the core texts in this area and a selection of less mainstream pieces, with the aim of engaging readers with contemporary debates which have reconfigured understanding of nationalism.